2006
DOI: 10.5424/sjar/2006043-198
|View full text |Cite
|
Sign up to set email alerts
|

Review. Specific detection of Listeria monocytogenes in foods using commercial methods: from chromogenic media to real-time PCR

Abstract: Listeriosis is one of the most important food-borne diseases. A variety of culture and rapid methods are available for the detection of Listeria spp. in foods. Although the presence of L. innocua may indicate potential contamination with L. monocytogenes, only the latter species is pathogenic for humans. Therefore, the most adequate tests are those which specifically detect L. monocytogenes. Chromogenic media is currently the most common method used for the presumptive identification of L. monocytogenes. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 65 publications
0
66
0
3
Order By: Relevance
“…hydrolyze esculin and the inclusion of esculin and ferric iron in enrichment or plating media results in the formation of an intense black color. We also know that the pathogenic species Listeria monocytogenes and Listeria ivanovii appear surrounded with an opaque halo zone on Ottaviani-Agosti media (8). Scotter and al., 2001 (9) showed that using only the standard method, a significant number of false negative results can be obtained when a large number of Listeria innocua was present in the samples.…”
Section: Discussionmentioning
confidence: 99%
“…hydrolyze esculin and the inclusion of esculin and ferric iron in enrichment or plating media results in the formation of an intense black color. We also know that the pathogenic species Listeria monocytogenes and Listeria ivanovii appear surrounded with an opaque halo zone on Ottaviani-Agosti media (8). Scotter and al., 2001 (9) showed that using only the standard method, a significant number of false negative results can be obtained when a large number of Listeria innocua was present in the samples.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of pathogenic strains with Listeria agar according to Ottaviani and Agosti (ALOA) detects the phosphatidylinositol-specific phospholipase C (PI-PLC) specifically for L. monocytogenes and L. ivanovii forming an opaque halo around the colonies in parallel with b-glucosidase activity (Greenwood, Willis, Doswell, Allen, & Pathak, 2005;Notermans, Dufrenne, Leimeister-Wächter, Domann, & Chakraborty, 1991). This phospholipase is encoded by the virulence gene plcA (Janzten et al, 2006;Reissbrodt, 2004). It is important to check ALOA plates after 24 h of incubation as the halo size increases rapidly so that negative colonies cannot be distinguished from positives.…”
Section: Listeria Selective Plating Mediamentioning
confidence: 99%
“…Due to its tolerance to live under extreme pH (some cultures grow at pH 9.6), temperature (<0e45 C) and salt conditions (tolerance up to 20% (w/v) NaCl), Listeria species can be found in a variety of environments, foods and clinical samples (Farber & Peterkin, 1991;Janzten et al, 2006;EFSA, 2007;Hof, 2003;Gandhi & Chikindas, 2007;Swaminathan, Cabanes, Zhang & Cossart, 2007). Due to the ubiquitous occurence of L. monocytogenes, a series of adaptations of its metabolism (Adrião et al, 2008;Gandhi & Chikindas, 2007;Greenacre, Brocklehurst, Waspe, Wilson, & Wilson, 2003;Hof, 2003;Sergelidis & Abrahim, 2009) is necessary to survive in difficult niches, resulting in an extensive regulatory repertoire (7% of Listeria genes are dedicated to regulatory proteins) (Buchrieser, Rusniok, Kunst, Cossart, & Glaser, 2003).…”
Section: Taxonomy and Special Propertiesmentioning
confidence: 99%
“…Pathogenic and nonpathogenic Listeria species can be differentiated by their activities of hemolysin or PI-PLC [87,88].…”
Section: Listeria Monocytogenesmentioning
confidence: 99%